CLINICAL AND INSTRUMENTAL CHARACTERISTICS OF PATIENTS WITH TYPE B DISSECTION OF THE DESCENDING THORACIC AORTA - Shkandala, Anna; Zelenchuk, Oleh; Todurov, Borys; Sikora, Normunds; Khokhlov, Andrii; Yashchenko, Nataliia; Kuzmych, Igor; Sudakevych, Serhii (Eastern Ukrainian Medical Journal, 2025)
Introduction. Aortic dissection (AD) is a disease associated with high mortality. This condition occurs due to a disruption in the structure of the aorta inner lining; blood penetrates into the thickness of the wall and dissects its inner and outer layers, forming an additional intravascular channel (false lumen). The most common classifications of AD are: DeBakey classification – dissecting aortic aneurysm is classified into 3 types depending on the origination of dissection and its duration; and the Stanford anatomical classification dividing AD into type A and type B. Despite the fact that this disease was introduced into clinical practice by Laennec back in 1819, the accumulation of knowledge regarding optimal methods of diagnosis and treatment of type B dissection was very slow and the management of this cohort of patients still remains quite controversial.The objective of our study was to analyze the features of clinical, laboratory and instrumental data of patients with dissection of the descending thoracic aorta (type B) under different treatment methods.Materials and Methods. This retrospective study included adult patients (≥18 years) who were hospitalized to the State Institution "Heart Institute of the Ministry of Health of Ukraine" between 2018 and 2024 for the descending thoracic aorta dissection. The main parameters evaluated were anthropometric data, demographic characteristics, medical history, comorbidities, laboratory data, and instrumental research results.Results. The study included 70 patients: 40 of them (group A) had underwent thoracic endovascular aneurysm repair (TEVAR) with best medical therapy (BMT) and 30 of them (group B) had been assigned best medical therapy (BMT) according to standard treatment methods. A typical profile of patients with descending thoracic aortic dissection in both groups was represented by a middle-aged or elderly man with concomitant arterial hypertension.In patients of group A as compared to group B, we observed a significantly higher (by 16.7%) creatinine level (p=0.044); a significantly lower (by 11.7%) glomerular filtration rate (78.9±21.7 ml/min versus 88.1±22.8 ml/min, p=0.033); pleural effusion was more frequent by 18.33% (10 (25.0%) versus 2 (6.67%), p=0.044). The following parameters were also found to be higher: the frequency of dissection spreading to the abdominal aorta (by 25.0%), the frequency of intramural hematoma (by 35.0%), the maximum diameter of the false lumen (by 30.9%, p=0.001). On the contrary: the maximum diameter of the true lumen was found to be smaller by 6.22% (p=0.031) compared to group B patients.Conclusions. Our study provides a better understanding of the clinical profile and prognosis in patients with type B aortic dissection under different treatment methods.